Hubungan Pemberian Susu Formula Dengan Kejadian Diare Pada Balita Di Puskesmas Tarempa Kabupaten Kepulauan Anambas - Pera, Hana (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
This study aims to determine the relationship between formula milk feeding and the incidence of diarrhea in toddlers at Tarempa Health Center, Anambas Islands Regency. The research used a quantitative method with a cross-sectional design. The subjects were mothers with toddlers aged 0–24 months, while the object was the incidence of diarrhea in toddlers. Data were collected through structured interviews using validated and reliable questionnaires. Data analysis techniques included univariate and bivariate analyses with the Chi-Square test. The results showed that out of 33 respondents, 73% of toddlers were given formula milk, and 64% experienced diarrhea. Bivariate analysis indicated a significant relationship between formula milk feeding and the incidence of diarrhea (p = 0.005). Toddlers who consumed formula milk had a higher risk of developing diarrhea compared to those who were not given formula. This study highlights the importance of educating mothers about exclusive breastfeeding and safe formula milk practices to prevent diarrhea in toddlers